Effectiveness of planned teaching programme on knowledge regarding dengue fever and its preventive measures among adult population in selected urban slums - Singh, Rupali; Kumar, Rohitash; Masood, Jamal (International Journal Of Community Medicine And Public Health, 2021)
Background: Dengue fever is the most critical mosquito-borne disease in the world caused by one of any of four serotypes of dengue virus. There has been a 30-fold increase in global incidence over the past fifty years. Epidemics of dengue result in human suffering, strained health services and massive economic losses. Methods: Quasi experimental one group pre-test-post-test research design was adopted to conduct the study among forty adults aged between twenty to 40 years residing in Janta Nagri, Urban slum, Lucknow, Uttar Pradesh, who matched the inclusion criteria were selected through non-probability purposive sampling technique. On day one pre-test followed by planned teaching programme was conducted and after seventh day post-test was taken. The data was analysed using descriptive and inferential statistics. Results: The results revealed that the mean post-test knowledge score was higher than mean pre-test knowledge score with standard deviation 20.15±4.02 and 7.67±3.11 respectively. The improvement of knowledge score is the mean difference of 12.5 which shows that there was a significant change in knowledge level of adult population. Conclusions: The study concluded that the planned teaching programme was effective in improving the level of knowledge regarding dengue fever and its preventive measures.